(untitled) (International relations and international law Journal, 2016)
In this article the author carries out the analysis of opinions of scientists-lawyers, tries to open an essence of private life. The main objective of jurisprudence – research of all aspects of private life. In this regard the author by the comparative analysis of practice of foreign countries, regulations of the Soviet period and the existing national legislation comprehensively investigated a ratio of concepts secret, personal secret, private secret, family secret. Including, on the basis of the analysis of the current legislation personal privacy investigates criminal legal protection and offers measures for its improvement.